(untitled) (Research, Society and Development, 2023)
Breast cancer is one of the most common types of cancer in the female population and its appearance is related to several factors, with genetic factors, related to mutations in genes, the most studied and with the greatest evidence in carcinogenesis. The discovery of mutations in genes that can lead to a higher incidence of this type of cancer was extremely important for the screening and early diagnosis of this type of tumor. Thus, this article aimed to carry out a bibliographical review of the current literature, from the last 5 years, with the purpose of answering the question “What is the influence of genetic factors on the development of breast cancer?”. For this, databases (BVS, SciELO, PubMed, EbscoHost and Google Scholar) were used. After the search, 22 articles met the inclusion requirements. The existence of mutations in specific genes such as BRCA1 and BRCA2, which are attributed to greater chances of developing this type of neoplasm, was verified. However, genetic mutations in other types of genes, such as TP53 and PALB2, will also be related to a higher incidence of breast cancer in people who carry these types of mutations. It was analyzed that the existence of these mutations, in specific genes, in women and in men, increases the incidence of prostate cancer and breast cancer, both female and male. It was found that greater investment in genomic studies is needed to universalize access to more specific technologies for cancer diagnosis and treatment.